Patent Pools, Litigation and Innovation - Jay Pil Choi; Heiko Gerlach (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper analyzes patent pools and their effects on innovation incentives. It is shown that the pro-competitive effects of patent pools for complementary patents naturally extend for dynamic innovation incentives. However, this simple conclusion may not hold if we entertain the possibility that patents are probabilistic and can be invalidated in court. In such a case, the licensing fees reflect the strength of patents. Patent pools of complementary patents can be used to discourage litigation by depriving potential licensees of the ability to selectively challenge patents and making them committed to a proposition of all-or-nothing in patent litigation. We show that if patents are sufficiently weak, patent pools with complementary patents reduce social welfare as they charge higher licensing fees and chill subsequent innovation incentives.
Keywords: O30; L10; L40; D80; K40; 330; patent pools; probabilistic patent rights; patent litigation; complementary patents